PENGARUH METODE PEMBUATAN HAY TERHADAP KANDUNGAN ASAM SIANIDA DAN KECERNAAN IN VITRO DAUN KETELA POHON KARET (Manihot glaziovii) - , MAULANA OSMAR SAKTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to study the effect of hay making treatment on ceara rubber leaves hydrogen cyanide content (HCN), chemical composition and its in vitro digestibility. The material used on this research was fresh ceara rubber leaves. There were two treatments and each treatment consisted of five replications. First treatment (A) was hay made by aerated withering. Second treatment (P) was hay making by drying it directly under the sun. Data taken included hydrogen cyanide (HCN), chemical composition, and in vitro digestibility. Data were analyzed with independent t-test. The results showed that second treatment (P) able to reduce the hydrogen cyanide (HCN) significantly (P<0.01). Hay with second treatment (P) has a lower content of HCN than first treatment (A) (230.63 vs 342.99ppm). while the chemical composition and in vitro digestibility showed were no significant difference (P> 0.05). dry matter (DM) digestibility and organic matter (OM) digestibility (respectively 61.62 vs 62.35%) and (59.60 vs 57.16%) The research conclusion that drying ceara rubber leaves driety under the sun decrease hydrogn cyanide (HCN) content with undirected treatment